Metabolic regulation of regulatory T cells: mechanisms, heterogeneity, and implications in disease - Getachew, Feven; Hu, Junhui; Benamar, Mehdi (Frontiers in Immunology, 2025)
Regulatory T (Treg) cells are essential for maintaining immune tolerance, preventing autoimmune responses, and supporting tissue repair. Tregs employ a flexible and diverse metabolic program that includes glycolysis, oxidative phosphorylation (OXPHOS), fatty acid oxidation, and lipid metabolism compared to conventional T cells, which largely rely on glycolysis to fuel their proliferation and function. This flexibility allows Tregs to adapt in different tissue environments while sustaining their suppressive activity. Thymic-derived (tTregs), peripheral (pTregs), and induced (iTregs) exhibit distinct metabolic profiles that influence their stability, proliferation, and suppressive capacity. These metabolic pathways are controlled by key regulators such as mTOR, LKB1, and Foxp3, while environmental cues, including nutrient availability, hypoxia, and microbiota-derived metabolites, further shape Treg function. Dysregulation of these pathways can compromise tolerance and contribute to immune-mediated diseases, chronic infections, cancer, and metabolic disorders. In this mini review, we summarize recent insights into the heterogeneity of Treg metabolism, highlighting how metabolic reprogramming underpins their immunoregulatory roles. We also explore therapeutic opportunities for targeting Treg metabolism and discuss future directions leveraging single-cell and spatial technologies to map context-specific metabolic programs in vivo.